Virtual reality-based technique for stress therapy - Mahalil I.; Rusli M.E.; Yusof A.M.; Yusof M.Z.M.; Zainudin A.R.R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Engineering; Industrial engineering; Stresses; 3-D environments; Comparative studies; Immersion; Immersive; Immersive VR; Malaysians; Treatment therapy; Virtual reality therapies; Virtual reality